A New Combined Parameter to Predict Premature Ventricular Complexes Induced Cardiomyopathy: Impact and Recognition of Epicardial Origin. (7th April 2016) - HAMON, DAVID; BLAYE‐FELICE, MARIE SADRON; BRADFIELD, JASON S.; CHAACHOUI, NAJIA; TUNG, RODERICK; ELAYI, CLAUDE S.; VASEGHI, MARMAR; DHANJAL, TARVINDER S.; BOYLE, NOEL G.; MAURY, PHILIPPE; SHIVKUMAR, KALYANAM; LELLOUCHE, NICOLAS
Predict the Impact of PVC on Myocardial Function: Introduction: Reversible premature ventricular complexes‐induced cardiomyopathy (PVC‐CMP) is a well‐described, multi‐factorial entity. Single predictors, such as PVC burden or QRS duration, may not apply equally to all patients in contemporary unselected populations including patients with structural heart disease (SHD) or with particular origin such as epicardial (EPI) PVC. We sought to evaluate clinical criteria associated with PVC‐CMP notably focusing on the EPI origin impact and ECG recognition and the value of a new composite predictor of PVC‐CMP, the PVC‐CMP‐Index. Methods and Results: We studied 107 consecutive patients (69 men; mean age = 56 ± 16 years) with frequent PVC (23.1 ± 11.5%) referred for PVC ablation. Thirty‐six patients (33.6%) had an underlying SHD and 25 patients (23.4%) an EPI PVC origin. After a mean follow‐up of 22.7 ± 15.3 months, 72.9% achieved a long‐term successful ablation and 54.2% had PVC‐CMP. PVC‐CMP prevalence was significantly higher in patients with an EPI compared to endocardial PVC focus (84.0% vs. 45.1%, respectively, P < 0.001). EPI PVC origin (OR = 68.7 IC95% [3.5–1363], P = 0.005), as well as SHD (OR = 12.3 IC95% [1.6–92.6], P = 0.015), was independent predictor of PVC‐CMP. While PVC burden (AUC = 0.78) or PVC‐QRS width (AUC = 0.68) independently predicted PVC‐CMP, the PVC‐CMP‐Index (values ≥39) defined as: PVC burden (0–1) × PVC‐QRS width (milliseconds) × a constant C (1.28 for SHD or 2 for ECG suggesting EPI origin based on our ECG 3‐step algorithm), highly correlated with PVC‐CMP (AUC = 0.91, sensitivity = 93%, specificity = 80%). Conclusion: We developed a new index, which incorporates PVC burden, QRS width, and presence of SHD or suspected EPI origin that best predicted PVC‐CMP.